THE ANALYSIS OF PERSONAL FACTORS CAUSING SUBSTANDARD ACT IN USING SELF PROTECTIVE EQUIPMENT FOR WELDING - Nitasya Ayu Alamanda Putri (Universitas Airlangga, 2019)
Welding is a job that has potential hazards and risks. An effort to reduce the risk of hazards in welding is by providing protection to workers in the form of Personal Protective Equipment (PPE) in accordance with the type of work. Substandard act is an action that can cause accidents. The purpose of this study was to analyze factors related to the incidence of substandard act done by welding workers in PT. INKA (Persero) in the use of PPE based on the ILCI Loss Causation Models theory. This study used observational technique with a cross sectional study design. The research respondents were 16 welding workers of assembling carbody division in PT. INKA (Persero). The data collections were done by using questionnaires and observation sheets with spearman correlation test analysis. The results of the statistical analysis in the study showed that age (r = -0,180), working period (r = -0,041), education level (r = 0,123), and knowledge (r = -0,391) had a weak relationship with substandard act of using PPE. The increase age, years of service, level of education and knowledge increased the tendency of workers to use PPE below the standard, while the higher level of education will increase the actions of workers in accordance with the standard use of PPE.Keywords: personal protective equipment, personal factor, substandard act